The science of tender passion: attempts to conceptualize love in the Ovidian tradition of the Middle Ages - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2020)
Devoted to the consideration of the theoretical constructions formed in the framework of the Ovidian Renaissance, reflecting the interpretation of love in the context of Western European culture at the turn of the 12th–13th centuries. The specific characteristics of the definition of love are revealed in the context of the treatises of this period.